2019
DOI: 10.3889/oamjms.2019.055
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Narrow Band Uvb (Nb-Uvb) In the Treatment of Pityriasis Lichenoides Chronica (PLC) In Vietnam

Abstract: AIM:This prospective clinical study presents the experiences with NB-UVB monotherapy in the treatment of PLC on Vietnamese patients.METHODS:We enrolled at National Hospital of Dermatology and Venereology (NHDV), Vietnam, 29 PLC patients with generalised disease involving at least 60% of the total body surface (based on Nine’s Rule) and/or failed to respond to other modalities of treatment. Patients were treated with NB-UVB followed the guideline of the psoriatic treatment of AAD-2010, three times weekly.RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…The majority of the patients in the current study did not develop any noticeable side effects that required discontinuation of the treatment with only 6% of patients developing irritation, this is less than the side effects reported by a study on 180 patients with PLC treated with nbUVB with 55% developing skin irritation 27 …”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The majority of the patients in the current study did not develop any noticeable side effects that required discontinuation of the treatment with only 6% of patients developing irritation, this is less than the side effects reported by a study on 180 patients with PLC treated with nbUVB with 55% developing skin irritation 27 …”
Section: Discussioncontrasting
confidence: 57%
“…The majority of the patients in the current study did not develop any noticeable side effects that required discontinuation of the treatment with only 6% of patients developing irritation, this is less than the side effects reported by a study on 180 patients with PLC treated with nbUVB with 55% developing skin irritation. 27 Although excimer light is a targeted treatment, it has been studied for several generalized conditions (e.g., Psoriasis, vitiligo, and atopic dermatitis). [28][29][30][31] It could be time consuming for the operator, however, if it offers better response and longer remissions than nbUVB then it is worth to be used.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable immunotherapeutic effect of NB‐UVB in PL might be explained by these anti‐inflammatory and immunologic alterations 16 . Several studies documented the efficacy of NB‐UVB 3,8,10,17,18 therefore it has been recommended as first‐line treatment option for generalized PL 4 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, CR was obtained in 66.7% of the PLC patients with a mean cumulative dose of 95 J/cm 2 and with a mean number of 51.2 sessions. Huu et al assessed the efficacy of NB‐UVB treatment with 29 PLC patients and reported that 82.8% of the patients achieved CR with a mean number of 13.8 sessions 17 . Fernandez et al have reported 8 adult PLC patients with diffuse involvement whose disease showed no response to topical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation